Hormônios bioidênticos para o alívio dos fogachos em mulheres na transição da menopausa: revisão Cochrane - Gaudard, Ana Marcia Iunes Salles [UNIFESP] (2017)
Objectives: To determine the effectiveness and safety of bioidentical hormone (BHT) therapy for the relief of vasomotor symptoms in women in the menopausal transition period compared to placebo or hormonal therapy with non-bioidentical hormones. Methods We used standard methodological procedures expected by the Cochrane Collaboration. The search was carried out in 2015 in the databases CENTRAL, PubMed, Embase and LILACS.The primary outcomes were vasomotor symptoms (hot flushes and night sweats). We evaluated the overall quality of the evidence using Grading of Recommendations Assessment, Development and Evaluation criteria (GRADE). Results: We included 23 RCTs (5779 participants), most were at risk of uncertain or low bias. The women treated with 17 beta-estradiol (BHT) adhesives had a significant reduction in the frequency (standardized mean difference-SDM -0.68, 95% confidence interval-CI -0.83 to -0.53, 4 RCTs, 793 women, low quality evidence) and intensity of hot flushes (mean difference-MD -19.94, 95% CI -24.86 to -15.02, 2 RCTs, 393 women, evidence of poor quality). It was not possible to perform meta-analyzes for comparisons between BHT gel or topical emulsion versus placebo, but all individual RCTs reported benefit in the THB group. The groups treated with oral BHT (SMD -0.80, 95% CI -1.03 to -0.57, 2 RCT, 356 women, evidence of poor quality) or intranasal route (MD -3.04, 95% CI -4, 05 to -2.03, 1 RCT, 458 women, evidence of moderate quality) had less hot flashes than the placebo group. It was not possible to perform meta-analyzes for comparisons between adhesive or oral BHT versus HT with conjugated equine estrogens (CEE), but all individual RCTs did not report differences between groups. Adverse events were more frequent in the BHT group than in the placebo group: oral use (OR 2.14, 95% CI 1.29 - 3.54, 9 RCT, 1822 women, low quality evidence), gel (OR 1, 41, 95% CI 1.09-1.83, 3 RCTs, 1086 women, moderate quality evidence) and intranasal (OR 1.96, 95% CI 1.26-3.03, 1 RCT, 458 women, evidence of quality moderate). There is no evidence of significant differences in the rate of adverse events in the comparisons between THB in transdermal emulsion or oral versus placebo or BHT adhesive and oral versus CEE. Conclusions: There was low to moderate quality evidence that BHT in various forms and doses is more effective than placebo for treating moderate to severe menopausal hot flushes in the menopausal transition period, but it is associated with a more incidence of adverse effects. There is no evidence of differences in the effectiveness and rate of adverse events of BHT compared to HT with CEE.